Effect of hyaluronate and splinting alone combined treatment (splinting and hyaluronate) on thumb carpometacarpal osteoarthritis - Salvatore Denaro; Salvatore Boccaccio; Antonino Zocco (Verduci Editore, 2020)
Thumb carpometacarpal osteoarthritis can lead to global hand dysfunctions and its symptoms are pain and inability. The purpose of this study is to determine the effectiveness of hyaluronate in relieving these symptoms, and to compare it to orthosis and combined treatment (orthosis and hyaluronate). We enrolled 39 patients, evaluated at the baseline by using numeric rating scale (NRS) for pain, Disability of the Arm, Shoulder and Hand (DASH) and Dreiser Scale for disability degree, and Digital Hydraulic Pinch Gauge for grip strength. Eligible participants were randomly assigned to one of the three treatments: injection of hyaluronate (group I), combined treatment (hyaluronate and orthosis, Group II) and orthosis (hard-resting splint, Group III). Patients of Group I and Group II were injected by low molecular weight Hyaluronate once a week for three consecutive weeks. Injections were performed by means of the so-called technique. The data analysis indicated a significant decrease (P<0.01) of pain at week 4, further manifested at week 26 by all groups treated. The same occurred for functional symptoms, and grip strength. This improvement appears more evident in group I that received HA.